Materials based on BIFEVOX and bismuth or iron simple oxides nanopowders - A. A. Krylov; Yu. V. Emelyanova; E. S. Buyanova; M. V. Morozova; A. I. Vylkov; A. Yu. Chuykin (Chimica Techno Acta)
Compositions of composite materials based on BIFEVOX and nanopowders of bismuth and iron oxides have been obtained. The absence of chemical interaction between the components has been proved, the total electrical conductivity of materials in the average temperature region has been determined. It has been shown that under the selected formation conditions, it has not yet been possible to achieve significant improvement of the functional characteristics of heterogeneous compositions in comparison with individual phases. However positive results on chemical and structural stability give way to further investigations.